The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/coatings12030339
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of HVOF Spray Process Parameters to Achieve Minimum Porosity and Maximum Hardness in WC-10Ni-5Cr Coatings

Abstract: High-velocity oxy-fuel (HVOF) spray coating plays a major role in many surface treatment methods, which tend to improve erosion and corrosion resistance properties. HVOF is well known for its dense and high-quality coating ability. This is due to the less in-flight exposure time, which tends to have less oxide content because of its high-velocity properties. Among the number of process parameters, porosity and hardness are predominant factors while considering wear rate and corrosion behaviour analysis. The cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Percentage) and maximum hardness (1325.26 HVx) [53]. Furthermore, a study found that the presence of the lowest porosity causes the Fe-based amorphous coatings to have the highest hardness [50]. These findings show that decreasing porosity leads to an increase in coating hardness.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Percentage) and maximum hardness (1325.26 HVx) [53]. Furthermore, a study found that the presence of the lowest porosity causes the Fe-based amorphous coatings to have the highest hardness [50]. These findings show that decreasing porosity leads to an increase in coating hardness.…”
Section: Resultsmentioning
confidence: 92%
“…Porosity causes inadequate coating cohesion and reduces the ability to endure indentation loads, resulting in a decrease in hardness. Furthermore, porosity in the coating can result in rising corrosion rates and wear [50]- [52]. The porosity of a coating is inversely related to its hardness.…”
Section: Resultsmentioning
confidence: 99%
“…The determination coefficient (R 2 ) is the measurement to determine the goodness of fit of the model. 60,61 The R 2 value always lies between 0 and 1, and a value higher than 0.75 represents a good fit for model. 62 The R 2 of the model showed a value of 0.9942, which was higher than 0.75, indicating the obtained results were well-matched with model prediction.…”
Section: Resultsmentioning
confidence: 97%
“…Surface plots and contour plots, which are indicators of potential independence of variables, have been established for the proposed empirical relation by taking into account two variables in the middle level and two variables in the x-and y-axes in order to obtain the affecting nature and optimized condition of the process on the UTS. The prediction of the response (UTS) for any zone of the experimental domain can be assisted by these response contours [34].…”
Section: Optimization By Response Surface Methodology Approachmentioning
confidence: 99%